Masquelet’s induced membrane technique in the upper limb: a systematic review of the current outcomes - Davide Pederiva; Lapo De Luca; Cesare Faldini; Luigi Branca Vergano (Journal of Orthopaedics and Traumatology)
Abstract Background The Masquelet induced membrane technique is a surgical procedure that allows the reconstruction of segmental bone defects using a relatively simple approach that requires minimal resources from both the healthcare facility and the patient. Historically applied to the lower limb, this technique is gaining increasing attention in the literature for its use in the upper limb. Methods A systematic review of the literature was conducted using the PubMed and Google Scholar databases to identify all studies reporting the outcomes of the Masquelet induced membrane technique in the long bones of the upper limb (humerus, radius, and ulna) with a sample size of at least 3 patients. The papers had to include the length of the bone defect, a description of the protocol used for treatment, the complications of each case, and the anatomical location of the defect. The studies that did not meet the above inclusion criteria were excluded. Results The search identified 1044 studies, of which 15 met the inclusion criteria. These studies described a total of 156 patients with a mean age of 42 years. The affected bone segments included the humerus in 22 cases and the forearm in 134 cases. In 108 cases, the bone defect was septic. The average defect length was 4.5 cm. PMMA was used as a spacer in all cases, with antibiotics added in 77% of them. The average time interval between the first and second phases of the procedure was 9.5 weeks, and bone union took an average of 5.5 months. The mean follow-up duration was 48 months, and the complication rate was 21%, ranging from 0% to 75%. Conclusions The Masquelet induced membrane technique is a viable surgical option for managing segmental bone defects of the upper limb. However, the complication rate remains significant. Further research is needed to identify strategies to improve the outcomes of this technique. Level of Evidence: Level 2.